Identyfikacja i wykorzystanie źródeł informacji w kształtowaniu wyników finansowych przedsiębiorstwa - Baran, Wioletta (Identification and Utilization of Information Resources in the Process of Designing Financial Results in Business Enterprises, 2005)
The aim of this article is to identify the systems and management procedures which can be used as information recourses in the process of decision making. The appropriate utilisation this resources supports management accounting and controlling in the creation of expected future financial results. The author claims that the most important issues in this field are: construction of the account scheme which is based on the organizational structure, responsibility centres and needs of managers, the possibility of simultaneously usage of different models of cost accounting in decision making, the current economic analysis, financial planing, budgeting and necessity of existing internal control and audit in business enterprises.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 11-22